Correction: Xiong et al. Probabilistic Tracking of Annual Cropland Changes over Large, Complex Agricultural Landscapes Using Google Earth Engine. Remote Sens. 2022, 14, 4896 - Sitian Xiong; Priscilla Baltezar; Morgan A. Crowley; Michael Cecil; Stefano C. Crema; Eli Baldwin; Jeffrey A. Cardille; Lyndon Estes (Remote Sensing, 2023)
In the original publication [...]